Voices of Unheard People in The Good Shopkeeper: A Contrapuntal Reading - Sharma, Rom Nath (Vox Batauli, 2023)
This paper analyzes Samrat Upadhyay’s short story, “The Good Shopkeeper” as a literary writing of postcolonial era using Edward Said’s contrapuntal reading strategy. This study aims to explore and assess the dark spots of the story, give voice to the unheard characters, and uncover new meanings and new aspects of the story. This study also explores how in the voices of the unheard people pertain the power and influence the decision. Moreover, this research paper investigates the inner incidents that took place in the story. It becomes clear that story is a manifestation of realism in the context of Nepal. Simultaneously, the study also reveals that it can be connected to the colonizers and colonized mindset in the post-colonial era and also how colonialism is ongoing process in the contemporary time.